A Review on The Realistic Mobility Models for Vehicular AD-Hoc Networks - S. Murugeswari,; G. Mahendran, (AG Volumes, 2022)
There has been an imperative rise in interest in Vehicular Ad-hoc Networks (VANETs) in both the academic and commercial arenas. In the research of VANETs, one of the problems is to define a model of vehicle mobility that provides an accurate and realistic description of vehicle movement at macro and micro levels. The ability to dynamically adjust vehicle mobility as a result of vehicular communication protocols is another problem. The community has come up with a variety of solutions to these two problems. For this reason, as well as the fact that there are so many models on the market claiming to be suitable for vehicle traffic, it is difficult to discern their genuine qualities, level of realism in relation to vehicular mobility, and actual capabilities.